Inhibitory effect of 6-phosphogluconate (6-PG) on NagS. - Chao Li (145513) (2025)
(a) Chemical structures of 6-PG and linear GlcNAc-6P. (b) Average Tm curve of NagS in presence of 6-PG. Melting curve of 4 µM NagS (black), 4 µM NagS with 2 mM 6-PG (large dash), 5 mM 6-PG (dot), and 10mM 6-PG (small dash). It was shown that when 6-PG concentration increases, a shift in Tm was shown. The two Tm peaks at 46.45 °C ± 0.4 and 58.0 °C ± 0.5 °C merged into a single peak at Tm 53.08 °C ± 0.03 °C in response to the addition of 10 mM 6-PG. (c) 6-PG detection by LC–MS. Reactions of 10 mM 6-PG with NagS (black) or deactivated NagS (red) were detected by LC-MS. Note that no 6-PG (m/z = 275.0176) was consumed in both conditions. (d) Evaluation of the inhibition of 6-PG on NagS activity. The activity of NagS (V0) was measured using 1 mM GlcNAc-6P as the substrate, with the addition of 0–4 mM 6-PG. (e) Competitive inhibition of NagS by 6-PG. The inhibition by 6-PG is presented as Lineweaver–Burk plot (Ki = 0.28 mM). (f) Effect of the addition of D-gluconate on GlcNAc sensitivity. Spores (5 × 105 CFU) suspension of S. coelicolor M145 nagB mutant was spotted on MM supplemented with 1% mannitol, 10 mM GlcNAc and a range concentration of D-gluconate, followed by incubation for 72 h at 30 °C. The data underlying this Figure can be found in S1 Data. (TIF)